Distribution and abundance of horseshoe crabs in Asajaya mangrove forest - Diana Bazila, binti Shahruzzaman (Universiti Malaysia Sarawak (UNIMAS), 2014)
A study on the distribution and abundance of horseshoe crabs was carried out at Asajaya mangrove forest, Sarawak. There were 52 individuals of horseshoe crab had been caught in three stations established; Asajaya Laut (n=8), Jemukan (n=14), and Sadong Jaya (n=30). There were two species identified which were Carcinoscorpius rotundicauda (n=31) and Tachypleus gigas (n=21) which come from family Tachypleine. The mean length and mean weight of total horseshoe crabs caught was 25.89 6.14 cm, 150.28 76.54 g and 28.31 9.57 cm, 330.33 231.33 g for male and female respectively. The length-weight relationship for both horseshoe crab caught showed a positive correlation (r=0.572). However, the length-weight relationship for male T.gigas (r=0.725) and female C.rotundicauda (r=0.284) showed negative correlation. The sediment analysis showed the highest contained of sediment was silt at all sampling sites and chi-square test showed there were a significance difference (P<0.05) between the grain size of sediments and distribution of horseshoe crabs. The physico-chemical analysis was done by using one-way ANOVA and showed significance difference (P<0.05) for all parameters studied (Temperature, dissolved oxygen, pH and salinity). Hence, the environmental variables (sediments and physico-chemical parameter) were important for distribution and abundance of horseshoe crabs.